Nickel-Catalyzed sp3 C–H Activation - Johnson, Colton E.; Li, Shangyu; Arora, Ramon; Mirabi, Bijan; Lautens, Mark (Synlett, 2023)
Base metal catalyzed C–H activation represents a highly atom economic method to access functionalized molecules. This Account will focus on Ni-catalyzed C–H activation of sp3-hybridized carbon atoms with a particular focus on mechanism, recent applications, challenges, and outlook in this area. This Account will primarily focus on recent mechanistic work from 2017–2023.1 Base Metal C–H Activation2 Nickel-Catalyzed sp3 C–H activation3 Differences between Ni and Pd4 Mechanistic Considerations5 Elementary Steps6 Directed sp3 C–H Activation7 Choice of Directing Group8 Primary C–H Activation9 Secondary C–H Activation10 Tertiary C–H Activation11 Conclusion and Outlook
Keywords: C–H activation; nickel; catalysis; mechanism; directing group